Muslims and Christians Debate Justice and Love - Katherine Bullock (International Institute of Islamic Thought, 2020)
Johnston, who spent over a decade as an evangelical clergyman in Algeria and a teacher in Egypt and the West Bank, hopes his book, Muslims and Christians Debate Justice and Love, will help reinforce the cooperative spirit between nations that seems to be diminishing in the contemporary world. Initially misled by the title, I was expecting the book to be a qualitative study based on interviews with Muslims and Christians debating justice and love. Instead it is a collection of chapters investigating how Christian and Muslim scholars separately have addressed these concepts over time. The book consists of seven chapters with a conclusion. We should commend Johnston on bringing together scholarship on these two virtues (justice and love) into a single volume. In this day and age, justice and love are often seen as separate entities. One can be just, but that might involve overlooking love. Love is often seen as a ‘touchy feely’ concept not suitable for serious scholarship, especially in relation to governance. By insisting that “justice and love are both complementary and inseparable” (2), and by tying both to governance, Johnston helps us appreciate the real-world implications of what happens when justice as love is missing. By seeing humanity’s failures in this regard, Johnston prompts us to do better. He insists that justice-love is essential for human flourishing.